2008
DOI: 10.1016/j.ejcts.2008.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive mitral valve surgery: a systematic review and meta-analysis

Abstract: The mitral valve has been traditionally approached through a median sternotomy. However, significant advances in surgical optics, instrumentation, tissue telemanipulation, and perfusion technology have allowed for mitral valve surgery to be performed using progressively smaller incisions including the minithoracotomy and hemisternotomy. Due to reports of excellent results, minimally invasive mitral valve surgery has become a standard of care at certain specialized centers worldwide. This meta-analysis quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
299
4
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 421 publications
(340 citation statements)
references
References 59 publications
15
299
4
9
Order By: Relevance
“…Five meta-analyses have already been performed on minimal invasive heart surgery. Modi et al (2008) showed that MIMVS was a safe and durable alternative to MS and was associated with equal mortality and neurologic events, less morbidity in terms of reduced incidence for re-operation for bleeding, a trend towards shorter hospital stay, less pain, and faster return to pre-operative function levels compared with conventional sternotomy, despite longer CPB time and ACCT. Ding et al (2012) evaluated ALMT in congenital heart disease and suggested that this had a longer CPB time and ACCT, but shorter intubation time, ICU time, and LOHS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five meta-analyses have already been performed on minimal invasive heart surgery. Modi et al (2008) showed that MIMVS was a safe and durable alternative to MS and was associated with equal mortality and neurologic events, less morbidity in terms of reduced incidence for re-operation for bleeding, a trend towards shorter hospital stay, less pain, and faster return to pre-operative function levels compared with conventional sternotomy, despite longer CPB time and ACCT. Ding et al (2012) evaluated ALMT in congenital heart disease and suggested that this had a longer CPB time and ACCT, but shorter intubation time, ICU time, and LOHS.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the question remains as to whether the potential benefits of a minimally invasive approach can outweigh the potential drawbacks of limited operative exposure, longer cardiopulmonary bypass time and aortic crossclamp time. One recent meta-analysis of minimal access mitral valve surgery (Modi et al, 2008), which collected data from 1996 to 2008, suggested some short-and long-term benefits for mortality, reoperation for bleeding, intensive care unit (ICU) stay, and hospital stay over conventional surgery, despite longer operative time. However, this meta-analysis included all kinds of minimally invasive approaches without any subgroups or randomized clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…In studies that included mainly redo operation patients [12][13][14], both ventricular fibrillation arrest and endoclamping were used, although direct clamping was reported in some cases in one series [12]. As in other reports [1,19], CPB time was significantly longer in the MIMVS group, but heterogeneity was evident as expected for continuous parameters. Overall meta-analysis also showed a reduced rate of postoperative AF with no heterogeneity.…”
Section: Commentmentioning
confidence: 98%
“…Cardiac surgeons have been mastering minimally invasive surgery techniques for several years with favorable results [1], and these benefits may be particularly evident in patients at high risk who, more than others, are prone to experience adverse events postoperatively. However, minimally invasive surgery may be associated with an increased incidence of stroke and aortic dissection, as well as significantly longer cardiopulmonary bypass (CPB) time [2], which can be classified as technical-or learning curve-related drawbacks.…”
Section: (Ann Thorac Surg 2015;-:---) ó 2015 By the Society Of Thoracmentioning
confidence: 99%
“…Several studies on video-assisted minimally invasive heart surgery have shown that, in spite of CPB and clamping time are longer when compared with the conventional technique via median thoracotomy, it is a safe procedure and is associated with a lower morbidity: less postoperative pain, less bleeding, time of extubation, ICU stay, and shorter hospital stay and return to activities more quickly [20][21].…”
Section: Discussionmentioning
confidence: 99%